Do Amapá ao Pará: uma rota pelos caminhos do Manejo Florestal Sustentável na Amazônia Legal - Bruno Rogério Silva Cavalcante; Silvana Aparecida de Souza (Confins)
This text aims to analyze social and economic factors of the Amazonian territories that make up a river route carried out by a medium-sized vessel. The main social and economic characteristics related to Sustainable Forest Management (SFM) were identified and analyzed in order to briefly elucidate the strengths and weaknesses of these municipalities. The sequence of these characteristics was organized according to the flow of the vessel during the journey, starting in the state of Amapá (Macapá and Santana) and passing through Pará (Gurupá and Porto de Moz) until reaching the Extractive Reserve (Resex) Verde para Sempre (green forever), area also from Pará. This work is the result of field research. On the occasion of the trip to the research field, we dedicated ourselves to taking photographs and collecting the necessary information to contextualize and analyze the referred river route, describing its results and the consequences of a work established as a result of the collective desire of the extractivists with regard to its correct timber production, following legality and strategically establishing the implementation of the SFM to achieve territorial development.